The Urgency of Ratification Draft Bill On Protection of Indonesian Domestic Workers: A Human Rights Perspective - M. Rizki Yudha Prawira; Davilla Prawidya Azharia; Aji Lukman Ibrahim; Anni Alvionita Simanjuntak (Universitas Muhammadiyah Malang, 2024)
Domestic workers are very vulnerable to various violations of labour rights, such as exploitation, low wages, unclear working hours, and uncertainty about work eligibility. This problem can be confirmed by data submitted by several institutions focusing on domestic workers' rights. According to the Indonesian Migrant Workers Union (SBMI), there are approximately 4 million domestic workers in the country, with 2.7 million facing labour rights violations and experiencing physical and sexual violence. Additionally, the National Domestic Workers Advocacy Network (Jala PRT) reported 2,148 cases of economic, physical, and psychological violence from 2015 to 2019. Komnas Perempuan recorded 2,344 cases of violence against domestic workers from 2005 to 2022, and received 29 direct complaints between 2017 and 2022, including reports of physical violence and unpaid salaries. Although the Republic of Indonesia Minister of Manpower Regulation No. 2 of 2015 addresses domestic worker protection, it lacks specific safeguards for their rights. Consequently, domestic workers are exceedingly vulnerable to various forms of discrimination and rights violations. Establishing legal protections at the statutory level is imperative to address these issues. Abstrak Pekerja rumah tangga sangat rentan terhadap berbagai pelanggaran hak-hak buruh, seperti eksploitasi, upah rendah, jam kerja yang tidak jelas, dan ketidakpastian kelayakan kerja. Permasalahan ini dapat dibuktikan melalui data yang disampaikan oleh beberapa lembaga yang fokus pada hak-hak pekerja rumah tangga. Menurut Serikat Pekerja Migran Indonesia (SBMI), terdapat sekitar 4 juta pekerja rumah tangga di negara ini, dengan 2,7 juta diantaranya menghadapi pelanggaran hak-hak buruh dan mengalami kekerasan fisik dan seksual. Selain itu, Jaringan Nasional Advokasi Pekerja Rumah Tangga (Jala PRT) melaporkan 2.148 kasus kekerasan ekonomi, fisik, dan psikis pada tahun 2015 hingga 2019. Komnas Perempuan mencatat 2.344 kasus kekerasan terhadap PRT pada tahun 2005 hingga 2022, dan menerima 29 pengaduan langsung pada tahun 2017. dan tahun 2022, termasuk laporan kekerasan fisik dan gaji yang belum dibayar. Meskipun Peraturan Menteri Ketenagakerjaan Republik Indonesia No. 2 Tahun 2015 mengatur tentang perlindungan pekerja rumah tangga, peraturan tersebut tidak memberikan perlindungan khusus terhadap hak-hak mereka. Akibatnya, pekerja rumah tangga sangat rentan terhadap berbagai bentuk diskriminasi dan pelanggaran hak asasi manusia. Membangun perlindungan hukum di tingkat undang-undang sangat penting untuk mengatasi permasalahan ini.